2007
DOI: 10.1007/s00044-006-0015-z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of novel 3-[5-ethyl-2-(2-phenoxy-ethyl)-pyridin]-5-substituted isoxazoline libraries via 1,3-dipolar cycloaddition and evaluation of antimicrobial activities

Abstract: A series of novel 3-[5-ethyl-2-(2-phenoxy-ethyl)-pyridin]-5-substituted isoxazolines were synthesized via 1,3-dipolar cycloaddition of in situ generated nitrile oxide from 4-[2-(5-ethylpyridyl)-ethoxy]-benzaldoxime with alkenes to obtain new heterocyclic libraries containing a pyridine moiety in addition to the isoxazoline ring. The newly synthesized compounds were screened for their antimicrobial activity and were compared with standard drugs. The compounds demonstrated potent to weak antimicrobial activity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…Recently, we have reported microwave-assisted synthesis of the antihyperglycemic drug rosiglitazone [16]. In continuation to our work on the synthesis of biologically active heterocycles [17,18], herewith, we are reporting as an efficient …”
Section: Introductionmentioning
confidence: 77%
“…Recently, we have reported microwave-assisted synthesis of the antihyperglycemic drug rosiglitazone [16]. In continuation to our work on the synthesis of biologically active heterocycles [17,18], herewith, we are reporting as an efficient …”
Section: Introductionmentioning
confidence: 77%
“…H-NMR, 13 C-NMR, MS studies, and elemental analysis provided the structure proof of the pyridazine derivatives. As expected, the cycloaddition was regioselective.…”
Section: Resultsmentioning
confidence: 99%
“…13 C-NMR spectra were measured on Bruker Avance (100 MHz) instrument. The chemical shifts are expressed in δ and following abbreviations were used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that several isoxazoline moieties possessed a wide spectrum of activities like PTP1B inhibitory activity (Ahmad et al, 2006), antimicrobial (Gaonkar et al, 2007), anti-influenza virus (Kai et al, 2001), antifungal (Basappa et al, 2003), glycoprotein IIb/ IIIa receptor antagonists (Sielecki et al, 2001), anti-HIV (Ichiba et al, 1993), spermicidal and anti-HIV (Srivastava et al, 1999), analgesic and anti-inflammatory (Habeeb et al, 2001), and b-adrenergic receptor antagonist properties (Conti et al, 1998). However, their role during stressful condition is unknown.…”
Section: Introductionmentioning
confidence: 99%